Cognitive biases influence clinical medicine practice - Piryani, Rano Mal; Piryani, Suneet; Piryani, Rajesh (Janaki Medical College Journal of Medical Science, 2019)
Cognitive biases are prevalent in the clinical practice and recognized cause of medical error. Error due to cognitive biases influences decision-making process of healthcare professionals. The causes of cognitive biases are varied. Clinician must understand the causes of cognitive biases and acknowledge the biases happening in clinical practice. Awareness of potential biases may help clinician improve patients’ care and minimize medico-legal risks. Machine learning applications have been tried for the avoidance of biases occurring in health professionals’ diagnostic and therapeutic decision-making process but machine learning algorithms may also be subject to biases. Machine learning research in this aspect continues. Clinicians must learn how to minimize the cognitive biases and take pragmatic approach and follow the good decision-making rules.